The Effects of Music and Breathing Exercises in Reducing the Physiological Symptoms of Stress - Nida, John; Grewal, Rupinder; Rodrigues Pereira, Sophie; Grayson, Shira; Alameda, David (Journal of Advanced Student Sciences (JASS), 2014)
This study analyzes and compares several methods of reducing stress following induced anxiety events. The physiological indicators of stress measured in this study are blood pressure, heart rate, and electrodermal activity (EDA). To induce anxiety, participants underwent an abbreviated Trier Social Stress Test. Following the stress phase, one group of participants (n=10) sat in silence, one group (n=10) listened to music, and the last group (n=10) performed a breathing exercise. The largest reduction in stress based on the physiological parameters was found in the group who listened to music, however, those who performed the breathing exercise exhibited the greatest reduction in heart rate. The implications of these results can extend to help provide techniques to reduce anxiety in everyday life events that are applicable to the population. While this study suggests promising results, the fairly small sample size utilized in this particular study encourages further, larger scale experimentation to verify conclusions.
An article that appeared in JASS, issue 2014
Keywords: blood pressure; breathing exercises; EDA; heart rate; meditation; music therapy; relaxation; stress; stress coping mechanisms